A Scaled Central Path for Linear Programming (Journal of Computational Mathematics, 2001)
Interior point methods are very efficient methods for solving large scale linear programming problems. The central path plays a very important role in interior point methods. In this paper we propose a new central path, which scales the variables. Thus it has the advantage of forcing the path to have roughly the same distance from each active constraint boundary near the solution.
Keywords: Central path; Interior point methods; Linear programming.